Exploring the Conditions That Have Led to a Rise in Mexican Immigration and Entrepreneurship in Liberal, KS - Nohely Ruiz, Zaira (Kansas State University, The Chapman Center for Rural Studies, 2016)
This paper seeks to explore the socioeconomic conditions among Mexican immigrants and emphasize the factors that have bred the rise of immigrant entrepreneurship—despite the political and economic systems being against their favor. It will do so via interviews and photographs.
Zaira Nohely Ruiz, “Exploring the Conditions That Have Led to a Rise in Mexican Immigration and Entrepreneurship in Liberal, KS,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/244.
Keywords: Dodge City; Mexican Entrepreneurs; Mexican Immigrants; Liberal; Zaira Nohely Ruiz; Garden City